Printed microwells with highly stable thin-film enzyme coatings for point-of-care multiplex bioassay of blood samples. Issue 12 (21st June 2015) - Zhang, Liting; Cao, Xiaodan; Wang, Lu; Zhao, Xueyan; Zhang, Songping; Wang, Ping
<x xml:space="preserve">Abstract</x> A paper-based colorimetric biosensor suitable for point-of-care bioassay of blood samples is developed using highly stable enzyme thin-film coatings confined within inkjet printed polymeric microwells.